Agents of change: integration of neuropedagogy in pre-service teacher education - Shvarts-Serebro, Inna; Ben-Yehudah, Gal; Elgavi-Hershler, Orit; Grobgeld, Etty; Katzof, Ayelet; Luzzatto, Efrat; Shalom, Maya; Zohar-Harel, Tamar (Frontiers in Education, 2024)
Neuropedagogy, an interdisciplinary field at the nexus of neuroscience, psychology, and education, seeks to enhance teaching and learning processes. This paper advocates for the integration of neuropedagogical principles into teacher training, underscoring the pivotal role educators play in influencing students’ brain development. Incorporating neuroscientific knowledge in teaching can optimize educational outcomes. We explore key neuropedagogical principles, and highlight global developments in neuropedagogy. Three strategic avenues for integrating neuropedagogy in teacher training are proposed: promoting innovative teaching practices in teacher training, encouraging neuropedagogical research, and explicitly teaching neuroscientific knowledge to pre-service teachers. Our conclusion emphasizes the invaluable contribution of neuropedagogy to education and calls for its inclusion in pre-service teacher training.